Pemanfaatan Limbah Sayuran Organik dan Limbah Feses Ayam Petelur Sebagai Media Dalam Budidaya Maggot (Hermetia illucens) - Yan Aditama; Oki Imanudin; Dini Widianingrum (Tropical Livestock Science Journal, 2023)
This research aims to determine the level of efficiency of processing organic vegetable waste and laying hen feces, as well as to obtain a comparison of media in producing the best maggots. The research was carried out experimentally using a Completely Randomized Design (CRD) consisting of five treatments and four replications. The types of treatment used are P0 (100% organic vegetable waste), P1 (75% organic vegetable waste + 25% laying hen feces), P2 (50% organic vegetable waste + 50% laying hen feces), P3 (25% vegetable waste organic + 75% laying hen feces), P4 (100% laying hen feces). The variables observed included maggot weight, media shrinkage and nutritional content which included water content, protein, fat, fiber, ash and Kcal/Kg energy. The research data were analyzed using analysis of variance (ANOVA) and tested further using Duncan's difference test. The results of the study showed that organic vegetable waste media and laying hen feces had a real influence on the maggot weight treatment with a weight of 268.90 grams for treatment P0 when compared with P2 114.47 grams, P3 75.82 grams and P4 65.72. The nutritional content of P2 media has a water content of 79.47%, protein of 45.80%, fat of 19.43%, fiber of 2.98%, ash of 20.56%, and energy of 4667 Kcal/kg and the lowest content in P4 has a water content of 69.41%, 27.85% protein, 11.98% fat, 6.89% fiber, 20.98% ash, and 4085 Kcal/kg energy. The conclusion is that the best weight of maggots is produced from 100% organic vegetable waste. The best nutritional content of maggots in a medium of 50% organic vegetable waste + 50% laying hen feces has the best nutritional content.